Analysis of diffusion coefficient using reversed-flow gas chromatography-a review - Khalid, K.; Zain, Sharifuddin Md; Khan, R.A. (2011)
Problem statement: Since the earliest publication on the technique, Reversed-Flow Gas Chromatography (RF-GC) has been used to determine physicochemical properties by measuring the value of one in the presence of another. The method is precise, accurate and simple compared to other conventional techniques. Approach: The experimental setup consists of a small modification of a commercial gas chromatograph, so that it includes a four- or six-port gas sampling valve and a simple cell placed inside the chromatographic oven. Results: This cell suppresses the effects of the carrier gas flow on the physicochemical occurrence taking place in the stationary phase. These phenomena pertain to rate coefficients and diffusion coefficients. Conclusion: The RF-GC methodologies can be considered as a wise instrumental approach to study the physicochemical phenomenon of liquid pollutants. It can be used to determine the rate coefficients and diffusion coefficients values of samples at various temperatures for the studies of environmental science and physical chemistry research areas. However, the methodologies are not restricted to the current fields of research. It is also relevant in the area of food chemistry, geochemistry, material science, nanotechnology, biological science and chemical technology. © 2010 Science Publications.